Benthic diatoms of Mekong River and its tributaries in northern and north-eastern Thailand and their application to water quality monitoring - Sutthawan Suphan (2018)
Biomonitoring of benthic diatoms was performed to assess the water quality of Mekong River and its tributaries in northern and north-eastern Thailand. Fourteen sampling sites along the river and its tributaries were investigated. Two hundred and fifty-two species in 53 genera of diatoms were recorded. Each sampling site had distinct water chemistry and other physical variables. Cluster analysis identified 11 groups at 80% similarity. The relationship between diatom community composition and water quality variables was determined by statistical techniques. A number of diatom species were found to be useful as indicators of some physico-chemical properties of water. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.